Stiffness and Anisotropy Characterization of Mechanically-compressed Cohesive Soils Using Directional Wave Propagation - Ranjpour, Deniz. (Tufts University. Tisch Library., 2020)
Thesis (Ph.D.)--Tufts University, 2020.; Submitted to the Dept. of Civil Engineering.; Advisor: John Germaine.; Committee: Laurie Baise, Richard Plumb, Keith Katahara, and Robert White.; Keyword: Civil engineering.; Compressional and shear wave velocity (Vp and Vs) measurement is a powerful tool to study material behavior including elastic stiffness. The elastic stiffness and stress-velocity-porosity characterization can facilitate safer well designs and improve seismic imaging interpretations. Also, the nondestructive nature of wave velocity measurements makes it possible to assess the characteristics of the same specimen as it is deformed over a significant stress range. This research focuses on the high porosity clay, transitioning into low porosity mudrocks, under pressure. Naturally occurring cohesive soil deposits are inherently anisotropic, most often transversely isotropic (TI). A novel directional velocity measurement technology was designed and fabricated using piezoelectric elements, allowing for meaurements of Vp in three and Vs in two directions. The velocities were measured on resedimented specimens, deforming (up to 25% axial strain) under K0-consolidation (vertical effective stress (σv) =1-10 MPa) in a triaxial cell. The triaxial P-wave velocities increased by nearly 300 m/s (+17%) while the S-wave velocities increased by 350 m/s (+250%). The measured velocities were used to calculate the TI stiffness and compliance matrices, which were in turn used to calculate the elastic stiffness parameters at different stress levels. The results showed very low P and S anisotropy (<0.1) in resedimented Gulf of Mexico-Eugene Island (RGoM-EI) and not much anisotropy change over the 9 MPa increase in σv. Another point of interest in this research was the wave velocity behavior in high porosity material (0.25- 0.45 porosity) under high pressures (10 MPa < σv). A second testing setup was developed for this purpose (TCRS) which was used to run K0-consolidation (σv =1-25 MPa) tests on resedimented specimens. Vertical Vp and Vs were measured throughout these tests, expanding the vertical velocity measurement range (1-10 MPa) on deformable material by 2.5 times. The TCRS results showed a 450 m/s (+26%) increase in the P-wave velocity and 550 to 600 m/s (+283% to +300%) increase in the S-wave velocities, depending on the material. Finally, the velocity measurements were compared to in-house and published data, suggesting an increas- ing velocity trend with decreasing porosity over 1-100 MPa vertical effective stress. Also, the anisotropy results were compared to some published data, pointing out the anisotropy dependency on porosity and velocity ratios.